Jumping Gall Wasp, California Jumping Gall Wasp, Jumping Oak Gall, Flea Seeds Neuroterus saltatorius Edwards (Insecta: Hymenoptera: Cynipidae) - Kirsten M. Prior; Jiri Hulcr (EDIS)
Includes: Introduction - Synonymy - Distribution - Description - Life Cycle - Hosts - Ecology - Damage - Management - Selected References